2000
DOI: 10.1002/(sici)1097-4679(200001)56:1<23::aid-jclp3>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Quid pro quo: Fee for services delivered in a psychology training clinic

Abstract: The present study evaluated the use of a sliding-fee scale at a training clinic for doctoral students in clinical psychology. A chart review of 209 individual therapy clients and a follow-up telephone interview of 87 of these clients were conducted. Results of the chart review revealed a client group of relatively low income, with only a very small number receiving social assistance or a disability pension. The follow-up survey found that the large majority of clients were satisfied with the fees charged. Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…In contrast, research has consistently found that the large majority of clients express high levels of satisfaction with mental health services (e.g., Perreault & Leichner, 1993). Although not reported in the results section of the current article, the authors also found that over 80% of their clients reported high levels of global satisfaction with the services they received and would return for service in the future or recommend the service to others (Aubry, Hunsley, & Vito, 1996). Given such findings, it seems likely that asking clients about their reasons for termination yields more informative and accurate perceptions of their therapeutic experience than is obtained through ratings of service satisfaction.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, research has consistently found that the large majority of clients express high levels of satisfaction with mental health services (e.g., Perreault & Leichner, 1993). Although not reported in the results section of the current article, the authors also found that over 80% of their clients reported high levels of global satisfaction with the services they received and would return for service in the future or recommend the service to others (Aubry, Hunsley, & Vito, 1996). Given such findings, it seems likely that asking clients about their reasons for termination yields more informative and accurate perceptions of their therapeutic experience than is obtained through ratings of service satisfaction.…”
Section: Discussionmentioning
confidence: 71%
“…Data for the study were obtained by a review of clients’ clinical files and telephone interviews of former individual psychotherapy clients. Details of these reviews not directly relevant to the current article are presented in Aubry, Hunsley, Josephson, and Vito (in press). Prior to conducting the study, approval for the study was obtained by the School of Psychology’s Human Research Ethics Review Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Na formação desses profissionais, o assunto honorários é muito pouco explorado, trazendo uma deficiência na prática clínica. Do mesmo modo, há carência desse tópico em planos de ensino e cursos de formação de psicoterapeutas (Aubry & Hunsley, 2000;Monger, 1998;Shields, 1997;Tudor, 1998). Nesse ínterim, Tudor e Worral (2002) salientam que os psicoterapeutas com pouca experiência, embora atuantes em sua profissão, geralmente sentem-se inseguros frente ao seu sustento e muitos se veem obrigados a trabalhar em outras áreas para manterem seus rendimentos.…”
Section: • 325unclassified
“…Além das dificuldades citadas e exemplificadas por diversos estudos efetuados acerca do tema dos honorários na relação psicoterapêutica (vide Aubry & Hunsley, 2000;Eizirik, 1989;Jacobs, 1986), convém acrescer outras que denotam as deficiências encontradas na graduação, as quais se refletem na prática dos psicólogos clínicos iniciantes e até mesmo dos mais experientes. Assim, uma pesquisa realizada pelo Conselho Federal de Psicologia em 1987 sobre o perfil do psicólogo brasileiro assinala que a formação complementar extrauniversitária do psicólogo clínico é constituída por um tripé formado por estudos teóricos, supervisões e análise pessoal e requer um vasto investimento temporal, financeiro e pessoal (Neto, 2004).…”
unclassified
“…The factors that influence treatment acceptability for diverse cultural groups that have been identified in the literature include culturally similar therapists, linguistic similarity of therapists, level of directiveness, level of self-disclosure, cultural responsiveness, and use of indigenous counseling processes (see Atkinson & Lowe, 1995). The fees of some psychotherapists may prevent some low-income clients from accessing those services (Aubry, Hunsley, Josephson, & Vito, 2000). Hence, cost and acceptability must be considered in determining the effective application of intervention research into the field, thereby making the intervention more acceptable and culturally congruent for diverse populations.…”
Section: Scientific Evidencementioning
confidence: 99%